2007
DOI: 10.1210/jc.2007-1185
|View full text |Cite
|
Sign up to set email alerts
|

Familial Risk Factors for Microvascular Complications and Differential Male-Female Risk in a Large Cohort of American Families with Type 1 Diabetes

Abstract: Context: Type 1 diabetes (T1D) complications are responsible for much of the disease morbidity. Evidence suggests that familial factors exert an influence on susceptibility to complications. Objectives:We investigated familial risk factors and gender differences for retinopathy, nephropathy, and neuropathy. Design and Setting:This study was a case-control design nested on a cohort of T1D families. We collected data (questionnaire, medical records) starting in 1988. Follow-up has been ongoing since 2004.Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
65
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 35 publications
5
65
0
1
Order By: Relevance
“…This increase in blood pressure is reversed by either exogenous estrogen, the GPR30 agonist G-1, or the AT 1 receptor antagonist olmesartan, suggesting that activation of the ACE-ANG II-AT 1 receptor axis is negatively influenced by the GPR30 estrogen receptor in this model (9,24). Clinical and experimental studies suggest that females are not afforded protection from diabetic pathologies including renal injury compared with males (4,6,19,29,50). The exact mechanism for the loss of protection is not known particularly in the setting of hypertension.…”
mentioning
confidence: 86%
“…This increase in blood pressure is reversed by either exogenous estrogen, the GPR30 agonist G-1, or the AT 1 receptor antagonist olmesartan, suggesting that activation of the ACE-ANG II-AT 1 receptor axis is negatively influenced by the GPR30 estrogen receptor in this model (9,24). Clinical and experimental studies suggest that females are not afforded protection from diabetic pathologies including renal injury compared with males (4,6,19,29,50). The exact mechanism for the loss of protection is not known particularly in the setting of hypertension.…”
mentioning
confidence: 86%
“…Previous studies have indeed shown an association with intermediate markers of cardiovascular disease such as carotid intima-media thickness (17) as well as with cardiovascular disease itself (13). Regarding microvascular complications, a family history of type 2 diabetes has been associated with diabetic retinopathy (18) and with diabetic nephropathy in some (13)(14)(15)18) but not all (11) studies. In the present study we did not observe any association between a parental history of type 2 diabetes and microvascular complications despite a long duration of type 1 diabetes and despite differences in the metabolic risk profile.…”
Section: Replication In the Dcctmentioning
confidence: 97%
“…Family history of cardiovascular risk factors is associated with increased risk of microvascular complications in the offspring (Monti et al, 2007;Seaquist et al, 1989). A high body mass index (BMI) represents another potential risk factor for microvascular complications in youth with type 1 diabetes (Stone et al, 2006).…”
Section: Other Factorsmentioning
confidence: 99%